Climate variability, communities’ perceptions and land management strategies in Lay Gayint Woreda, Northwest Ethiopia - Menberu Teshome; Addisu Baye (Brawijaya University, 2018)
Climate variability is the fluctuation of climatic elements from the normal or baseline values. Agrarian communities are the most sensitive social groups to climate variability and associate extreme weather-induced hazards due to the fact that climate variability affects the two most important direct agricultural production inputs, such as rainfall and temperature. As Ethiopia is heavily dependent on agriculture its economic development is being hindered by climate variability coupled with many other deriving forces. Therefore, the objective of this study is to examine climate variability, local communities’ perceptions and land management strategies to reduce the adverse impact of climate variability in Lay Gayint Woreda, Ethiopia. Both primary and secondary data were used to complete this study. Primary data were collected and analyzed from a total of 200 randomly selected respondents reside in different agro-ecological areas. Metrology data were gathered from Nefas Mewcha Station from the years 1979 to 2010. Standardized rainfall anomaly index (SRAI), crop diversification index (CDI) and other descriptive statistical techniques were used to analyze the data. The results obtained from the climate data revealed an increase in temperature, and decrease and/or erratic in rainfall distribution. Time series SRAI from 1979 to 2010 indicates that 2002 and 2008 were characterized by extreme and severe dry conditions in order of importance with high impact on crop yields whist only 1984 and 1990 received near normal rainfall amount. Similarly, the survey result reveals that out of the total household heads, 87.5 % perceived that there was an increase in temperature over the last 20 years. The survey result also disclosed that significant numbers of households are more likely to adopt different land management strategies to reduce the negative impact of climate variability. Constructing terraces and check dams as well as planting trees were the major land management strategies used by the local communities. However, crop diversification index (CDI) was found to be 0.11 as the cultivated area is stanch to one crop indicating very low alternative crop production in the study area. Although the study area receives variable and inefficient rainfall the rugged topography and poor soil conditions have hindered the development of irrigation facilities. Local context-specific integrated watershed management activities, small-scale irrigation schemes and extension services need to be strengthened to reduce the impact of climate variability. Policy makers need also to substantially invest in establishing information dissemination systems in order to provide reliable weather information for farmers given that crop production is largely dependent on it.